Association of primary open-angle glaucoma with mitochondrial variants and haplogroups common in African Americans - Collins, David W. (Mol Vis, 2016)
PURPOSE: To estimate the population frequencies of all common mitochondrial variants and ancestral haplogroups among 1,999 subjects recruited for the Primary Open-Angle African American Glaucoma Genetics (POAAGG) Study, including 1,217 primary open-angle glaucoma (POAG) cases and 782 controls, and to identify ancestral subpopulations and mitochondrial mutations as potential risk factors for POAG susceptibility. METHODS: Subject classification by characteristic glaucomatous optic nerve findings and corresponding visual field defects, as defined by enrolling glaucoma specialists, stereo disc photography, phlebotomy, extraction of total DNA from peripheral blood or saliva, DNA quantification and normalization, PCR amplification of whole mitochondrial genomes, Ion Torrent deep semiconductor DNA sequencing on DNA pools (“Pool-seq”), Sanger sequencing of 3,479 individual mitochondrial DNAs, and bioinformatic analysis. RESULTS: The distribution of common African haplogroups within the POAAGG study population was broadly similar to prior surveys of African Americans. However, the POAG case population was found to be enriched in L1c2 haplogroups, which are defined in part by missense mutations m.6150G>A (Val83Ile, odds ratio [OR] 1.8, p=0.01), m.6253C>T (Met117Thr, rs200165736, OR 1.6, p=0.04), and m.6480G>A (Val193Ile, rs199476128, OR 4.6, p=0.04) in the cytochrome c oxidase subunit 1 (MT-CO1) gene and by a variant, m.2220A>G (OR 2.0, p=0.01), in MT-RNR2, which encodes the mitochondrial ribosomal 16s RNA gene. L2 haplogroups were predicted to be overrepresented in the POAG case population by Pool-seq, and the difference was confirmed to be significant with Sanger sequencing, that targeted the L2-associated variants m.2416T>C (rs28358580, OR 1.2, p=0.02) and m.2332C>T (OR 1.2, p=.02) in MT-RNR2. Another variant within MT-RNR2, m.3010G>A (rs3928306), previously implicated in sensitivity to the optic neuropathy-associated antibiotic linezolid, and arising on D4 and J1 lineages, associated with Leber hereditary optic neuropathy (LHON) severity, was confirmed to be common (>5%) but was not significantly enriched in the POAG cases. Two variants linked to the composition of the gut microbiome, m.15784T>C (rs527236194, haplogroup L2a1) and m.16390G>A (rs41378955, L2 haplogroups), were also enriched in the case DNA pools. CONCLUSIONS: These results implicate African mtDNA haplogroups L1c2, L1c2b, and L2 as risk factors for POAG. Approximately one in four African Americans have these mitochondrial ancestries, which may contribute to their elevated glaucoma risk. These haplogroups are defined in part by ancestral variants in the MT-RNR2 and/or MT-CO1 genes, several of which have prior disease associations, such as MT-CO1 missense variants that have been implicated in prostate cancer.